Megaprojects in Cabo Delgado: a look from the perspective of environmental displacements - Machanguia , Ana (Revista da UI_IPSantarém, 2023)
When we talk about the mozambican economy today it is almost impossible not to look at the importance of megaprojects in this process, since with the explosion of natural resources the configuration of the provinces and the country in general took new approaches both socially and economically and environmentally. In this context, when we look at the nature of the researched theme, we assume that we cannot speak of internally displaced people without looking at the impacts that megaprojects have on this layer of Mozambican society. This research aims to analyze from an environmental and economic point of view the impacts of the implementation of megaprojects in Cabo Delgado on the lives of internally displaced people. The research is relevant for the country in particular and for the international community in general because, for sustainable development, awareness is needed about how natural capital (natural resources) is implemented and exploited without destitution of their extinction or the transformation of the environment. This work used the type of bibliographic research through literature consultation related to the theme allied to the qualitative approach, under the perspective of the analytical and comparative method. The lack of access to vital coastal natural resources, internal displacements are concerns that local communities have with the implementation of megaprojects (Cunha, 2019), Internal migrations, environmental, social, cultural impacts, territorial disputes (Mussagy: 2013) wars and conflicts between low-income individuals Wise (2018) are challenges for the province.